Effects of retroversion and anteversion alignment in cemented hip arthroplasty / Nabila Aznan - Aznan, Nabila (2019)
Arthritis is a joint disease or known as a joint failure that normally occurs due to wear at the cartilage where the part that protecting the bone end. Total Hip Arthoplasty (THA) is a procedure where damage bone (femoral head and acetabulum) will replace with a hip prosthesis. Cemented Hip Arthoplasty is one of the alternative choice of a treatment. There are some risk might be happen during the surgery such as mil-alignment.